Disturbed Blood Flow Acutely Increases Endothelial Microparticles and Decreases Flow Mediated Dilation in Patients With Heart Failure With Reduced Ejection Fraction - Silva, Thiago O. C.; Sales, Allan R. K.; Araujo, Gustavo S. M.; Fonseca, Guilherme W. P.; Braga, Pedro G. S.; Faria, Diego; Rocha, Helena N. M.; Rocha, Natalia G.; Lima, Marta F.; Mady, Charles; Negrão, Carlos E.; Alves, Maria Janieire N. N. (Frontiers in Physiology, 2021)
Introduction: Disturbed blood flow, characterized by high retrograde and oscillatory shear rate (SR), is associated with a proatherogenic phenotype. The impact of disturbed blood flow in patients with heart failure with reduced ejection fraction (HFrEF) remains unknown. We tested the hypothesis that acute elevation to retrograde and oscillatory SR provoked by local circulatory occlusion would increase endothelial microparticles (EMPs) and decrease brachial artery flow-mediated dilation (FMD) in patients with HFrEF. Methods: Eighteen patients with HFrEF aged 55±2 years, with left ventricular ejection fraction (LVEF) 26±1%, and 14 control subjects aged 49±2 years with LVEF 65±1 randomly underwent experimental and control sessions. Brachial artery FMD (Doppler) was evaluated before and after 30 min of disturbed forearm blood flow provoked by pneumatic cuff (Hokanson) inflation to 75 mm Hg. Venous blood samples were collected at rest, after 15 and 30 min of disturbed blood flow to assess circulating EMP levels (CD42b-/CD31+;flow cytometry). Results At rest, FMD was lower in patients with HFrEF compared with control subjects (p<0.001), but blood flow patterns and EMPs had no differences (p>0.05). The cuff inflation provoked a greater retrograde SR both groups (p<0.0001). EMPs responses to disturbed blood flow significantly increased in patients with HFrEF (p=0.03). No changes in EMPs were found in control subjects (p>0.05). Disturbed blood flow decreased FMD both groups. No changes occurred in control condition. Conclusion: Collectively, our findings suggest that disturbed blood flow acutely decreases FMD and increases EMP levels in patients with HFrEF, which may indicate that this set of patients are vulnerable to blood flow disturbances